Enhanced growth and development of Chrysanthemum morifolium in microponic system under light-emitting diodes - Tung, Hoang Thanh; Nam, Nguyen Ba; Huy, Nguyen Phuc; Phuong, Truong Thi Bich; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
This paper investigated the growth and development of Chrysanthemum shoots in microponic systems in comparison with shoots in micropropagation system. A microponic culture system, combining micropropagation and hydroponics, could reduce the drawbacks of micropropagation system such as reduction of infection, saving of labor, material, space, etc. In this study, Chrysanthemum morifolium shoots with 3 cm in length were cultured in MC (microponic system with circular container - 12 cm diameter at top, 9 cm diameter at bottom and 8.5 cm in height), MR (microponic system with rectangular box - 8.5 cm in height, 35 x 28 cm at top and 30 x 25 cm at bottom) and micropropagation system (MO - rectangular plastic box with 800 ml of half-strength MS medium containing 30 g/l sucrose and 8 mg/l agar). The results indicated that shoots pretreated with 500 ppm IBA, cultured in MC (15 shoots per container) and ventilated with millipore membrane (MillisealTM, pore size 0.5 µm of diameter 2 cm) under 70% red LED combined with 30% blue LED gave thebest plant height, number of roots, fresh weight, and chlorophyll content (a, b and a+b) (5.18 cm, 12.50, 0.52 g, 28.19 µg/g, 13.56 µg/g and 41.75 µg/g, respectively). The survival rates of plants derived from MC and MR in the greenhouse were higher than those in MO (100%, 100% and 85%, respectively). This study indicated that MR was an effective and simple system for large-scale production of Chrysanthemum morifolium.